2015
DOI: 10.1007/s11747-015-0459-0
|View full text |Cite
|
Sign up to set email alerts
|

Disfluent vs. fluent price offers: paradoxical role of processing disfluency

Abstract: Conventional wisdom and prior research on processing fluency suggest that consumers prefer fluent information, such that it has positive effects on their purchase decisions. Challenging this conventional wisdom, and on the basis of recent research on processing disfluency, this study proposes that the increased effort required to process disfluent price information can lead to deeper information processing. If the advertised price offer represents a good value, it can enhance purchase decisions, even if custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
1
16
0
1
Order By: Relevance
“…Moreover, we demonstrated that experiencing a personal event that is not aligned with dispositional tendency led people to reconsider and modify their initial responses. This is somewhat consistent with recent findings in research on processing fluency in that feelings of disfluency change individuals' style and pattern of psychological responses [29,30] but is different from the findings about superior effects of "fit" [37]. Future research is called upon to address this issue in a systematic manner.…”
Section: Summary Of Findings and Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, we demonstrated that experiencing a personal event that is not aligned with dispositional tendency led people to reconsider and modify their initial responses. This is somewhat consistent with recent findings in research on processing fluency in that feelings of disfluency change individuals' style and pattern of psychological responses [29,30] but is different from the findings about superior effects of "fit" [37]. Future research is called upon to address this issue in a systematic manner.…”
Section: Summary Of Findings and Implicationssupporting
confidence: 83%
“…More specifically, if prevention-focused individuals experienced a positive personal event before making their donation decision, their likelihood to donate will increase relative to when experiencing a neutral or no event (i.e., baseline). This is because experiencing a positive event allows them to reconsider and modify their initial tendency that was negative toward donations to the direction that their experience suggests [29,30]. In contrast, experiencing a negative event confirms the dispositional inclination of prevention-focused individuals, and, thus, they do not feel the need to change their responses.…”
Section: The Moderating Effect Of Personal Eventsmentioning
confidence: 97%
“…Consumers use a variety of price‐related visual cues as they evaluate the prices of products (Grewal, Roggeveen, & Nordfält, 2014). Past research has shown several cues, such as the size of the fonts in which prices are presented (Coulter & Coulter, 2005), types of the fonts (fluent vs. disfluent) in which prices are presented (Mead & Hardesty, 2018; Motyka, Suri, Grewal, & Kohli, 2016), the distance between regular and sale prices (Coulter & Norberg, 2009), the presence of cents and commas in prices (Coulter, Choi, & Monroe, 2012), the presence of numbers that are of personal relevance to consumers (e.g., birthdate; Coulter & Grewal, 2014), vertical versus horizontal placement of prices (Choi & Coulter, 2012; Feng, Suri, Chao, & Koc, 2017), rounded versus precise prices (Thomas, Simon, & Kadiyali, 2010), and colors of prices (Puccinelli et al, 2013) among others. Particularly, the use of color red with prices is widely prevalent in retail.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Only when the product color matches the product type well, the interaction of product–background color combinations and product types can improve the consumers' product evaluation; but when the product color does not match the product type, the effect is no longer significant. This is because the disfluent experience caused by the product color that does not match the product type will make consumers consciously pay attention to the product color and process the product color deeply (Mead & Hardesty, 2017; Motyka et al, 2015). Then the product color and the background color will be separated, and the similar or contrastive relationship of product–background color combination will no longer be perceived from the common visual effect perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when product color matches with product type well (such as using functional colors for functional products), the choice of color will be perceived appropriated and fluent (Diemandyauman, Oppenheimer, & Vaughan, 2011; Lewis & Walker, 1989). Consumers will no longer split the background color because of influent product color (Motyka, Suri, Grewal, & Kohli, 2015). The product color and background color presented in the same interface will still be regarded as a whole by consumers.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%